Primary vs secondary prophylaxis with pegfilgrastim for the reduction of febrile neutropenia risk in patients receiving chemotherapy for non-Hodgkin's lymphoma: cost-effectiveness analyses. (January 2014) - Hill, Gregory; Barron, Richard; Fust, Kelly; Skornicki, Michelle E.; Taylor, Douglas C. A.; Weinstein, Milton C.; Lyman, Gary H.
Abstract Objective: Evaluate the cost-effectiveness of primary vs secondary prophylaxis (PP vs SP) with pegfilgrastim to reduce the risk of febrile neutropenia (FN) in Non-Hodgkin's Lymphoma (NHL) patients receiving myelosuppressive chemotherapy from a US payer perspective. Methods: A Markov model was used to compare PP vs SP with pegfilgrastim in a cohort of patients receiving six cycles of cyclophosphamide, vincristine, doxorubicin, and prednisone (CHOP) or CHOP plus rituximab (CHOP-R) chemotherapy. Model inputs, including efficacy of pegfilgrastim in reducing risk of FN and costs, were estimated from publicly available sources and peer-reviewed publications. Incremental cost-effectiveness was evaluated in terms of net cost per life-year saved (LYS), per quality-adjusted life-year (QALY) gained, and per FN event avoided over a lifetime horizon. Deterministic and probabilistic analyses were performed to assess sensitivity and robustness of results. Results: Lifetime costs for PP were 5000 greater than for SP; however, PP was associated with fewer FN events and more LYs and QALYs gained vs SP. Incremental cost-effectiveness ratios (ICERs) for PP vs SP for CHOP were 13, 400 per FN event avoided, 29, 500 per QALY gained, and 25, 800 per LYS. CHOP-R results were similar (15, 000 per FN event avoided, 33, 000 per QALY gained, and 28, 900 per LYS). Results were most sensitive to baseline FN risk, cost per FN episode, and odds ratio for reduced relative dose intensity due to prior FN event. PP was cost-effective vs SP in 85% of simulations at a 50, 000 per QALY threshold. Limitations: In the absence of NHL-specific data, estimates for pegfilgrastim efficacy and relative risk reduction of FN were based on available data for neoadjuvant TAC in patients with breast cancer. Baseline risks of FN for CHOP and CHOP-R were assumed to be equivalent. Conclusions: PP with pegfilgrastim is cost-effective compared to SP with pegfilgrastim in NHL patients receiving CHOP or CHOP-R.